The Financial Performance's Mediating Role in Environmental, Social, and Governance (ESG) and Firm Value (Global Journal of Management and Business Research, 2024)
As corporate practices grow more sustainable due to increased global awareness one of the key factors in assessing companies is the Environmental Social and Governance ESG framework ESG data and other sustainability-related information are thought to have the power to affect company value The study s objective is to investigate the impact that ESG has on a company s value using financial performance as a mediating factor Regression data analysis techniques are used in this study to examine the relationship between the variables This study made use of secondary data from the OSIRIS and Thomson Reuters databases 97 businesses that met the purposive sampling requirements made up the sample and 582 observations were made during the 2018 2023 timeframe Firm value cannot be impacted by ESG but financial performance can be impacted by ESG and financial performance can influence firm value The whole mediating influence that financial success has on the relationship between ESG and business value is also demonstrated by the results a study design that explains the relationship between ESG and business value through the mediation of financial performance
Keywords: ESG; financial performance; firm value